THE FUTURE OF CONSCIOUSNESS. - STRATE, LANCE (ETC: A Review of General Semantics, 2016)
The author discusses the future of consciousness, and reviews the past and present of consciousness. Topics include understanding consciousness based on people's subjective examination of one's own consciousness, the notions of spirits, supernatural consciousnesses, and conceptions of the divine, and the parallel between the universe of the spirit and the universe of information.